Non artheritic bilateral anterior ischaemic optic neuropathy (NAION) as devastating complication following Total Hip Arthroplasty: a case report: Bilateral visual loss following total Hip Arthoplasty - Manzotti, Alfonso; Schianchi, Alice; Pace, Lucia; Salvadori, Giuliano; Biazzo, Alessio; Cerveri, Pietro (Acta Biomedica Atenei Parmensis, 2019)
Introduction: Postoperative vision loss (PVL) is an extremely rare complication following major surgical procedures. Patients with systemic hypertension, diabetes, coronary diseases and smokers are generally predisposed to this complication. More frequently, it is caused by ischemic optic neuropathy (ION), central retinal artery occlusion or retinal vein occlusion. Rare cases of unilateral PVL following total joint arthroplasty surgery have been recently described in literature. Case report: This case report describes the first reported bilateral non-arteritic anterior ischemic optic neuropathy (NAION), which occurred 3 days following a total hip arthroplasty with a consequent post-operative hypotension. Conclusions: Orthopedic surgeons should be aware that in hip joint replacement procedures, selected patients present an higher risk of ION following intra/postoperative hypotension and prolonged surgical times. (www.actabiomedica.it)